Access to and use of finance for pastoralists facing droughts in Somalia - Diriye, Abdishakur (Jameel Observatory for Food Security Early Action, 2024)
Presented at Jameel Observatory for Food Security Early Action Community of Practice meeting, Nairobi, 14-15 May 2024